Aplikasi Inseminasi Buatan pada itik Magelang di Dusun Sempu, Desa Ngadirojo,Kecamatan Secang, Kabupaten Magelang - Yosephine Laura Raynardia; M S. I. Pradipta; Y I Pratama; Z Ayun (Media Kontak Tani Ternak, 2020)
This service aims to arouse the interest of the residents of the Dusun Sempu village as the original location of the distribution of Magelang ducks to re-breed Magelang ducks to increase the population while improving their economic conditions. The decline in Magelang duck population is attributable to the large number of populations sold out without the addition of population through breeding. The lack of breeding is due to the low interest of the people in Magelang duck. From 1994 to 2007, the Sempu Hamlet, Ngadirojo Village, Secang sub-district, Magelang Regency were the centers of breeding to selling of Magelang ducks, but because of the monetary crisis, the chaotic climate and the low interest of the next generation resulted the breeding process are not continued. Artificial Insemination service in ducks is expected to be able to educate the generation of Sempu Hamlet Youth Association so that their interest in breeding of the ducks increases. This education is also expected the livestock group to be more intense in conducting duck breeding. Artificial Insemination is a cheap and easy technology that can be applied to the community to increase egg fertility. Hopefully the number of Day Old Duck (DOD) can increase and finally able to increase the duck population in the Sempu Hamlet area. Improving the community's economy can be done by marketing cultivation products, such as the sale of DOD, meat and eggs.